2005
DOI: 10.1055/s-2005-871541
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Chemoselective Cross-Coupling of Primary and Secondary Alkyl Halides with Arylzinc Reagents

Abstract: Functional-group-compatible cross-coupling reaction of alkyl halides with arylzinc reagents takes place under iron catalysis in the presence of TMEDA, producing a variety of aromatic compounds in good to excellent yield. The pronounced effect of a magnesium salt was found to be the key to the promotion of the iron-catalyzed coupling reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(60 citation statements)
references
References 3 publications
2
52
0
6
Order By: Relevance
“…3 mmol), magnesium turnings (628 mg, 25.9 mmol), 1,2-dibromoethane (0.15 mL, 1.6 mmol), one small crystal of iodine, THF (60 mL) and zinc chloride (7.7 mL of 1.0 m solution in dry Et 2 O, 7.7 mmol) were used to prepare bis(3,4-methylenedioxyphenyl)zinc. [52] This was added dropwise over 5 min to a suspension of the 2-methoxy salt (4, X= OMe) (778 mg, 2.0 mmol) in THF (20 mL) Following the general method A, a portion (480 mg, 1.30 mmol) of this product was treated with TFA (1.0 mL, 13 mmol) and addition of ammonium hexafluorophosphate (500 mg, 3.07 mmol) in water (2 mL) gave 28 as a yellow powder (410 mg, 64 %). For NMR data, refer to Using a combination of the typical methods [8,21,53] for the complexation of 1,4-dienes, [Fe(CO) 5 ] (81 mL, 0.61 mol) was added to 1,2-dimethoxycyclohexa-1,4-diene [54] (67 g, 0.48 mol) in di-n-butyl ether (540 mL), and the mixture was heated at reflux for 16 h, using an oil bath temperature of 152-157 8C.…”
mentioning
confidence: 97%
“…3 mmol), magnesium turnings (628 mg, 25.9 mmol), 1,2-dibromoethane (0.15 mL, 1.6 mmol), one small crystal of iodine, THF (60 mL) and zinc chloride (7.7 mL of 1.0 m solution in dry Et 2 O, 7.7 mmol) were used to prepare bis(3,4-methylenedioxyphenyl)zinc. [52] This was added dropwise over 5 min to a suspension of the 2-methoxy salt (4, X= OMe) (778 mg, 2.0 mmol) in THF (20 mL) Following the general method A, a portion (480 mg, 1.30 mmol) of this product was treated with TFA (1.0 mL, 13 mmol) and addition of ammonium hexafluorophosphate (500 mg, 3.07 mmol) in water (2 mL) gave 28 as a yellow powder (410 mg, 64 %). For NMR data, refer to Using a combination of the typical methods [8,21,53] for the complexation of 1,4-dienes, [Fe(CO) 5 ] (81 mL, 0.61 mol) was added to 1,2-dimethoxycyclohexa-1,4-diene [54] (67 g, 0.48 mol) in di-n-butyl ether (540 mL), and the mixture was heated at reflux for 16 h, using an oil bath temperature of 152-157 8C.…”
mentioning
confidence: 97%
“…[41] Interessanterweise ist es für eine erfolgreiche Kreuzkupplung erforderlich, das Diorganozinkreagens aus einem Grignard-Reagens herzustellen (Schema 20). Die Gegenwart eines Magnesiumsalzes, das bei der Erzeugung der Diorganozinkverbindung anfällt, scheint für die Umwandlung notwendig zu sein.…”
Section: Negishi-kupplungunclassified
“…Iron-catalyzed cross-coupling reactions of alkyl electrophiles are not limited to organomagnesium compounds [51]. Nakamura et al reported the successful application of diarylzinc reagents employing FeCl 3 and TMEDA in THF at 50 C as preferred catalyst [52]. To circumvent the dissipation of one aryl group of the diarylzinc reagent, Knochels methodology to introduce the dummy ligand Me 3 SiCH 2 has been applied successfully (Table 5.10, entries 2 and 3).…”
Section: Cross-coupling Reactions Of Alkyl Electrophiles J165mentioning
confidence: 99%